The Application and Assessment of Textile Dye Golden Yellow HER by Bacteria and its Impact on Seed Germination - Bharati Y. Taware; Chhaya D. Sonar; Amarja H. Bhosale (The Bioscan, 2025)
Two-way Multivariate Analysis of Variance (MANOVA) is a statistical method used to assess how two independent variables jointly influence two or more continuous dependent variables. It allows for the evaluation of both main and interaction effects. In the present study, two-way MANOVA was applied to investigate the biodegradation of a textile dye. The textile industry uses a substantial amount of dyestuffs for fabric coloration, and a large portion of these dyes is discharged through effluents, posing serious environmental hazards. Conventional effluent treatment methods are often ineffective in completely removing such dyes, making biological degradation a preferred alternative. In this research, the commonly used textile dye Golden Yellow HER was selected, and five newly isolated bacterial strains (GYH-1 to GYH-5) were evaluated for their biodegradation potential. These strains were obtained from acclimatized samples and identified using morphological, biochemical, and 16S rRNA sequencing techniques. Quantitative enzymatic activity assays revealed that both bacterial strain and incubation time had significant effects on enzyme activity, with a significant interaction between the two factors as well. The enzymes considered for present study are Azoreductase, Manganese Peroxidase, and Laccase Furthermore, phytotoxicity studies were conducted on Jowar and Mung seeds, where two parameters two parameters radicle length and plumule length are considered. It is also statistically tested whether the treated dye water, after degradation, is as safe for plants as distilled water. KEYWORDS: Biodegradation, Golden Yellow HER, MANOVA, two-way ANOVA, enzyme activity, phytotoxicity